Comparison of RTSP and UDP Protocols in Supporting UAV Video Streaming in a Limited Network Environment - Mar’atus Suci Novitasari; Muhamad Syariffuddien Zuhrie; Agus Wiyono; Fendi Achmad; Sayyidul Aulia Alamsyah (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study examines the performance comparison between the Real Time Streaming Protocol (RTSP) and the User Datagram Protocol (UDP) in supporting UAV real-time video streaming within constrained network environments. The research aims to identify which protocol provides better transmission quality when network limitations such as restricted bandwidth, high latency, and fluctuating connectivity occur. The methodology involves capturing and analyzing Quality of Service (QoS) parameters including latency, jitter, throughput, and packet loss under simulated limited-network conditions. Wireshark and controlled bandwidth-limiting scenarios were used to measure protocol behavior during video transmission. The results indicate that UDP achieves lower latency and higher throughput due to its lightweight and connectionless nature, making it more efficient for real-time applications but more susceptible to packet loss in unstable network conditions. In contrast, RTSP, operating over TCP, provides more reliable data delivery with significantly lower packet loss but introduces higher latency and jitter, which may affect real-time responsiveness. These findings offer guidance for selecting an appropriate protocol based on UAV mission requirements and network availability, ensuring more adaptive and efficient video streaming performance in constrained environments.